Analyzing distortion contributions in a complex device model. Issue 4 (1st July 2014) - Rahkonen, Timo; P. Aikio, Janne
Abstract : Purpose: – The purpose of this paper is to propose a method to reduce the non-linear distortion of a transistor to its input and output ports to aid distortion contribution analysis (DCA). This is especially needed when the internal structure of a device model is complex. Design/methodology/approach: – The non-linear distortion generated by all non-linear sources inside a device model are reduced to transistor i/o ports by LMSE fitting techniques. Simulations of an LDMOS power transistor are used to compare the reduced distortion results with the actual non-linear sources. Findings: – It is shown, that device models where the current sources are split by intermediate nodes cause superficial results, when distortion contributions are calculated as a superposition of contributions from individual non-linear sources. The proposed iterative fitting technique works. Research limitations/implications: – Some non-quasistatic effects and the transfer functions from external terminals to internal controlling nodes are not covered. Practical implications: – The analysis is a step toward a generic non-linear distortion contribution simulation tool that would aid the designers to develop more linear analog circuits. Originality/value: – The concept of DCA itself is fairly new. This paper makes a step to represent the distortion sources in a canonical way.